Leveraging Big Data Analytics to Enhance Water, Sanitation, and Hygiene (WASH) Systems - Adhikari, Binod Kumar; Mahajan, Ramesh (Amrit Research Journal, 2024)
The Water, Sanitation, and Hygiene (WASH) sector is crucial to public health and achieving sustainable development goals. To enhance the effectiveness of WASH initiatives, it is essential to gather data from various sources, including Flow Monitoring, Water Point Mapping (WPM), mWater, Leak Detection (FMLD), and mWash. By implementing big data analytical tools such as Apache Hadoop and Apache Spark, this sector can efficiently store, process, and analyze large volumes of unstructured data within a distributed, parallel computing environment. Leveraging big data analytics in the WASH sector enables improved monitoring, visualization, equitable data-driven decision-making, post-implementation tracking, open data practices, and strengthened social accountability, ultimately supporting the sector’s development and sustainability.